Support of Electronic Commercial Entities In the Conditions of Deepening Global Corona Crisis: Tax Aspect - Kovalenko, Yuliia Mykhailivna; Boreiko, Nataliia Mykolaivna; Skoromtsova, Tetyana Oleksandrivna; Panura, Yuliia Vasylivna; Boreiko, Oleksandr Yuriiovych (Sustainable Economic Development and Advancing Education Excellence in the era of Global Pandemic, 2020)
The article reveals topical issues of improving the taxation of e-commerce entities in the global economic crisis caused by the spread of corona virus infection COVID-19. The purpose of the article is to study the current state of e-commerce in Ukraine and identify possible ways of improving taxation of activity subjects in the situation of deepening corona crisis. The article is based on general scientific methods of cognition: abstractlogical, dialectical and system analysis, induction and deduction, analogy and extrapolation, as well as logical generalization. Ecommerce is a promising activity that has been showing steady growth for many years. The ability to do business online allows many businesses to adapt to new business conditions, including quarantine restrictions imposed by the spread of corona virus COVID-19. E-commerce is one of the types of economic activity, which is developing and at the same time it is also a reliable source of budget, despite the crisis. However, the economic crisis has faced with businesses in this area, so these ones need state support. The potential of e-commerce is significant. It allows its subjects to reorient its activity depending on the needs of the business environment. We should take into account this feature when we develop measures to support this area and provide conditions for its sustainable growth. The proposed measures will increase the number of online stores, turnover from operations in this area and sales of goods via the Internet, the number of taxpayers and tax revenues to the state budget, as well as reduce the amount of concealment of income from transactions.

Стаття розкриває актуальні питання вдосконалення оподаткування суб'єктів електронної комерції в умовах глобальної економічної кризи, спричиненої поширенням коронавірусної інфекції COVID-19. Метою статті є дослідження сучасного стану електронної комерції в Україні та визначення можливих шляхів удосконалення оподаткування суб'єктів діяльності в умовах поглиблення коронакризи. В основу статті покладено загальнонаукові методи пізнання: абстрактно-логічний, діалектичний та системний аналіз, індукція та дедукція, аналогія та екстраполяція, а також логічне узагальнення. Електронна комерція - перспективний вид діяльності, який вже багато років демонструє стабільне зростання. Можливість вести бізнес онлайн дозволяє багатьом підприємствам адаптуватися до нових умов ведення бізнесу, в тому числі до карантинних обмежень, спричинених поширенням короновірусу COVID-19. Електронна комерція - один з видів економічної діяльності, який розвивається і водночас є надійним джерелом наповнення бюджету, незважаючи на кризу. Однак економічна криза зіткнулася з бізнесом у цій сфері, тому він потребує державної підтримки. Потенціал електронної комерції є значним. Вона дозволяє її суб'єктам переорієнтовувати свою діяльність залежно від потреб бізнес-середовища. Цю особливість слід враховувати при розробці заходів з підтримки цієї сфери та забезпечення умов для її сталого зростання. Запропоновані заходи дозволять збільшити кількість інтернет-магазинів, обороти від операцій у цій сфері та продажу товарів через мережу Інтернет, кількість платників податків та податкові надходження до державного бюджету, а також зменшити обсяги приховування доходів від операцій.
Keywords: E-Commerce; COVID-19; Corona Crisis; Business Entities; Taxation; електронна комерція; COVID-19; коронакриза; суб’єкти господарювання; оподаткування